An Analysis Of Deletion Strategy In TranslationOf The Novel The Rainbow Troops - Wicaksono, Hermianto Purbo (2012)
The objectives of the study are to describe the linguistic form deletion strategy in translating The Rainbow Troops and to explain the equivalence and non equivalence the message found in translation of The Rainbow Troops. The writer analyzed one of the strategies that translator used in translating based on tanslation rules. The writer employs descriptive qualitative method. By this method, the writer uses the translating The Rainbow Troops novels to be the data source. As the comparison, there are also data from the novel in Indonesian language. The technique of the data collection is documentation. The results of this research show that: first, there are four linguistic forms of deletion used by the the translator in translating. The writer finds 250 data. There are 183 or 73.2% data belong to words, 18 or 7.2% data belong to phrase, 31 or 12.4% data belong to clause, 18 or 7.2% data belong to sentence. Second, from 250 data. There are 232 or 92.8% data belong to equivalence, 18 or 7.2% data belong to non equivalence data.